DIFFERENCES OF CULEX SPP AND AEDES SPP LARVAE MORTALITY RATES ON THE USE OF THEMEFOS - Wahyu Darmawan (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2021)
Eradication of the mosquito vectors that cause several diseases is still being carried out today where methods are still being developed. This research aims to identify the mortality rate of Culex spp. and Aedes spp. larvae for the use themefos or abate with sowed and wrapped of filter paper. The author uses quasi-experimental to observe that mortality. The design was devided into two groups, giving themepos/abate with a national dose of (1gr/10 liters of water) in 24 hours with threatment sowed and wrapped of filter paper through the analysis of varians/annova test to observe the varians of the time of mortality of Culex spp. and Aedes spp. larvae as well as probit analysis to see the probability of time of the larvae’s death.The result of this research is no defference in the mortality of Culex spp. and Aedes spp. larvae for the uses of themefos/abate with sowed and wrapped of filter paper. The authors suggestion is giving themefos or abate by wrapping filter paper preverably for larvae in a stagnant water such as Aedes spp larvae because it does not provide residual granules in water reservoirs used for human activities while the used of themepos/abate with sowed can also be used for a stagnant water or has a small discharge.